2015
DOI: 10.1007/s00436-015-4468-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative characterization of microRNAs in Schistosoma japonicum schistosomula from Wistar rats and BALB/c mice

Abstract: More than 40 kinds of mammals in China are known to be naturally infected with Schistosoma japonicum (S. japonicum) (Peng et al. Parasitol Res 106:967-76, 2010). Compared with permissive BALB/c mice, rats are less susceptible to S. japonicum infection and are considered to provide an unsuitable microenvironment for parasite growth and development. MicroRNAs (miRNAs), via the regulation of gene expression at the transcriptional and post-transcriptional levels, may be responsible for developmental differences be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Sja-miR-1 was abundant in Schistosoma japonicum and considered playing an important role in schistosome sexual maturation (Cai et al, 2013;Han et al, 2015). This study provides the following evidence that the sja-miR-1 is involved in the occurrence and progression of hepatic fibrosis during schistosome infection: (1) sja-miR-1 was present in HSCs and involved in host HSC activation by targeting the Sfrp1;…”
Section: Discussionmentioning
confidence: 69%
“…Sja-miR-1 was abundant in Schistosoma japonicum and considered playing an important role in schistosome sexual maturation (Cai et al, 2013;Han et al, 2015). This study provides the following evidence that the sja-miR-1 is involved in the occurrence and progression of hepatic fibrosis during schistosome infection: (1) sja-miR-1 was present in HSCs and involved in host HSC activation by targeting the Sfrp1;…”
Section: Discussionmentioning
confidence: 69%
“…Previous studies have shown that the sequences of some schistosomal miRNAs are conserved; they are homologous with those of other species including mice, rats and other hosts and may carry out similar biological functions . In addition, a study by Hu et al.…”
Section: Mirnas May Regulate the Establishment Of Schistosome Infectimentioning
confidence: 97%
“…miRNAs also modulate the response to pathogens by affecting the inflammatory response, autoimmune disorders and metabolic disorders . Recently, an increasing number of schistosome miRNAs have been identified with conventional cloning methods and the deep‐sequencing technique in S. japonicum and S. mansoni, in different developmental stages including cercariae, schistosomula, adult worms and eggs . Differential expression of certain miRNAs has been observed between schistosomes from different developmental stages, or between male and female worms, as well as between hosts with different susceptibility to schistosome infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with permissive BALB/c mice, rats are less susceptible to S. japonicum infection and are considered to provide an unsuitable microenvironment for parasite growth and development. Forty-one differentially expressed miRNAs have been identified in comparisons of rats and mice (Han et al, 2015). One hundred sixty-two miRNAs are expressed in M. fortis in mice, with 12 in the liver, 32 in the spleen and 34 in the lung being differentially expressed in M. fortis (Han et al, 2013).…”
Section: Epigenetic Studies In Schistosomes: What Is Known?mentioning
confidence: 99%